Synthetic cell-based patterning systems and their applications in stem cell differentiation - Glykofrydis, Fokion (The University of Edinburgh, 2020)
Pattern formation underpins cell specification, tissue organization, and morphogenesis during embryonic development. Tissue engineering strategies based on stem cell differentiation and organoid formation attempt to recapitulate developmental patterning, but suffer from variable efficiency, limited complexity, and anatomical disorganization. Whereas considerable research has focused on understanding patterning in vivo, bottom-up efforts in engineering synthetic niches to control patterning in vitro have been limited. This thesis explores a synthetic biology-based approach to create self-organizing mammalian cell systems, and use them as signalling centres for stem cell applications. The first half of the thesis explores whether integrin-ligand heterotypic adhesions can drive the formation of hyperuniform patterns. HEK-293 derivative cell lines were bio-engineered to overexpress heterophilic cell adhesion molecules in a drug-inducible manner using CRISPR genome editing. Transgenic systems were characterized in input sensitivity, output strength, adhesion properties, and their ability to form hyperuniform distributions. The second half of the thesis explores applications of self-organizing cell systems to control stem cell decisions. A pre-established phase-separation patterning system was modified to produce WNT3A from multicellular groups, which self-organize with mouse embryonic stem cells and elicit polarized signalling events. When differentiated in self-organizing co-cultures, embryonic stem cells exhibit enhanced and spatially controlled mesoderm induction in 2D and 3D conditions respectively, due to exogenous, localized Wnt signalling. WNT3A producers can also trigger nephrogenesis in mouse metanephric mesenchyme, demonstrating their wider applicability. This work provides novel prototype platforms and conceptual approaches to control developmental cell fate decisions and organization in vitro, contributing to the generation of synthetic niches.
Keywords: protein-signal WNT3A; cultured stem cells; integrin-ligand heterotypic adhesions; hyperuniform patterns; CRISPR genome editing; WNT3A